PENGARUH UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP PROFITABILITAS DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Wedhana Purba, Ida Bagus Gde Indra; Yadnya, I Putu (E-Jurnal Manajemen, 2015)
Industry must maintain alignment relation to society by taking into account social responsibility (CSR) which is very important for the company's activities. CSR is intended that the business is able to reduce the negative impact of the company on social and environmental aspects. Research on CSR has been investigated and showed differences in the results. This observation test CSR and profitability are affected by the variable size of the company and leverage the manufacturing company in Indonesia Stock Exchange. Method of sampling is done the method nonprobability purposive sampling techniques also. Based on these criteria obtained a sample of 66 companies. Methods of data collection in this observation is non participant observation method. This observation using path analysis with the results of firm size and leverage positive effect on profitability, size of firm positive effect on leverage, and firm size, leverage, and profitability positive effect on CSR
Keywords: Corporate Social Responsibility (CSR), firm size, profitability, leverage